2019
DOI: 10.1039/c9ra02665g
|View full text |Cite
|
Sign up to set email alerts
|

Application of natural deep eutectic solvents to extract ferulic acid from Ligusticum chuanxiong Hort with microwave assistance

Abstract: In this study, natural deep eutectic solvents (NADES) combined with microwave-assistance extraction (MAE) were researched to establish an environmentally-friendly method for extracting ferulic acid from Ligusticum chuanxiong Hort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…Although no significant differences were observed among the conventional solvents MeOH and EtOH 80 and the choline chloride (CC) and lactic acid (LA)-based NADES in the extraction of rosmarinic acid, the green solvents, namely CC:U and CC:LA, were more efficient to extract ferulic acid than MeOH and EtOH 80. Similar results were obtained by Xie et al [ 47 ] being CC:U the best solvent for extracting ferulic acid ( p < 0.05) compared to other NADES and conventional solvents. Other authors reported CC:U (1:2) as an excellent solvent for the extraction of compounds from other genus, namely rutin from Sophora japonica [ 48 ], 3,4-dicaffeoylquinic acid from Lonicerae japonicae Flos [ 49 ] and tyrosol from extra-virgin olive oil [ 50 ].…”
Section: Resultssupporting
confidence: 87%
“…Although no significant differences were observed among the conventional solvents MeOH and EtOH 80 and the choline chloride (CC) and lactic acid (LA)-based NADES in the extraction of rosmarinic acid, the green solvents, namely CC:U and CC:LA, were more efficient to extract ferulic acid than MeOH and EtOH 80. Similar results were obtained by Xie et al [ 47 ] being CC:U the best solvent for extracting ferulic acid ( p < 0.05) compared to other NADES and conventional solvents. Other authors reported CC:U (1:2) as an excellent solvent for the extraction of compounds from other genus, namely rutin from Sophora japonica [ 48 ], 3,4-dicaffeoylquinic acid from Lonicerae japonicae Flos [ 49 ] and tyrosol from extra-virgin olive oil [ 50 ].…”
Section: Resultssupporting
confidence: 87%
“…Alternatively, natural deep eutectic solvents (NADES) have also been applied [12,[20][21][22][23][24][25][26] for this purpose. In general, many multicomponent liquid mixtures, such as NADES [27][28][29][30][31][32], ionic liquids [30,[33][34][35], and organic solvent mixtures [36][37][38] are considered as promising green solvents. Another reason for binary solvents research is the optimization of reactants concentrations and crystallization efficiency [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…30 Although many studies reported ineffective extraction at water contents greater than 50% (v/v), some studies showed that using 60% (v/v) water in NADESs was effective, even if not the best. 22 In this study, AMW60 showed a higher extraction yield for MS (21.7 AE 0.03 mg g À1 dry weight) and AS (12.7 AE 0.03 mg g À1 dry weight) than conventional solvents (distilled water, aqueous EtOH, and absolute EtOH) (Table 4). Interestingly, the developed NADESs could extract a high yield of MS and AS in a shorter time than previous reports with EtOHbased MAE, providing MS and AS of 23.09 mg g À1 and 10.76 mg g À1 dry weight, respectively.…”
Section: Independent Variablesmentioning
confidence: 60%
“…20 According to NADESs as effective and safe solvents, NADESs are combined with extraction techniques assisted by microwave and ultrasound. 21,22 For fumaric acid extraction using NADESbased MAE, the extraction yield is higher than that of the heating method, and MAE takes 12 times less time than the heating method. 22 In addition, the combination of NADESs with ultrasound-assisted extraction is efficient for anthocyanin extraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation